ChemInform Abstract: Indium Trichloride Catalyzed sp3 C—H Bond Functionalization of 2‐Alkyl Azaarenes under Microwave Irradiation. Issue 16 (April 2015) - Chatterjee, Sourav; Bhattacharjee, Pinaki; Temburu, Jagadeesh; Nandi, Debkumar; Jaisankar, Parasuraman
Abstract An enantioselective version of the presented functionalization of 2‐methyl and 2‐ethyl quinolines as well as 2‐methylpyridine with enediones and eneamides is currently in progress.